Administration of improvements in matrix income management for better performance - Tofoli, Eduardo Teraoka; Santos, Andre Ponce dos; Tófoli, Irso; Silva, Íris Bento da (Revista Gestão da Produção Operações e Sistemas, 2008)
Companies that sell their products in markets in fierce competition must have resources or tools that help inanalysis and control, and have the objective of verifying whether the company is reaching expected results, if itis meeting its targets in a given period, or if it is experiencing problems with sales and needs to take remedialaction. It is necessary for businesses that identify with this scenario of competition to acquire, or even create,machinery or tools to help in Matrix Income Management. These tools are used at a refrigerator company, inthe whole group and in every segment in which it operates, which helps in strategic planning in maximizingrevenues through sales, and the realization of profit. This tool is based on three pillars: commercial organizationas a whole, customers and production. If any problem occurs in one of the three pillars, the tool identifies it,making it much easier to resolve these problems by those responsible for managing them. The company that usesthis tool can more easily achieve its goals.Key-Words: Administration of Improvement; Matrix Income Management; Performance.